AN ANALYSIS OF DERIVATIONAL SUFFIXES ON "PERCY JACKSON THE SEA MONSTER" NOVEL BY RICK RIORDAN - Umi Masitoh; Lilia Indriani (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2021)
The English word formation in morphology in this analysis will investigate the morphology of English word formation in this research. The form, purpose, and meaning of derivational suffixes in the novel were the study's problems. This research aims to figure out what kind of derivational suffixes there found in the data source. The data for this analysis came from Rick Riordan's E-book novel Percy Jackson and the Sea Monster. The data in this study was collected using the documentation process. This study's data was analyzed using a qualitative approach. The study revealed four derivational suffix types: nominal Suffix, verbal Suffix, adjectival Suffix, and adverbial Suffix. Based on the observation and readings of the e-novel of the study, the purpose of the study is to describe word-forming the derivational Suffix and what the Suffix that mainly uses by Rick Riordan's in the novel Percy Jackson and the Sea Monster. The researcher found four derivational suffixes from the novel: verb, adverb, noun, and adjective. Moreover, the data collected from the novel are 363 data of words forming the derivational Suffix.